European Investment Bank’s financial assistance to Lithuania and its role in economy transformation - Galinienė, Birutė; Bumelytė, Junona (Publishing House of the Wrocław University of Economics, 2009)
The main purpose of this article is to generalize the EIB experience in financing projects in Lithuania. The object of this article is the influence of the EIB loans on Lithuanian economic transformation. The authors present first a general overview on the role of the EIB, lending objectives and benefits of the EIB financing and review the main products and services provided by the Bank, paying special attention to a new financial engineering instrument recently developed by EIB. The second part of the article presents a general overview of international institution’s activities in Lithuania concentrating on the major infrastructure projects developed in Lithuania. Finally the authors assess the global financial turmoil and implications for the EIB role in Lithuania. (fragment tekstu)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 59, s. 181-190